Diet of the grass lizard Microlophus thoracicus icae in the Ica river valley, Peru - Pérez Z., José (2015)
The diet of grass lizard, Microlophus thoracicus icae, was evaluated in three localities of the Ica River Valley, Peru. The dietary pattern was characterized by high consumption of vegetable material, mainly Prosopis spp. leaves, and invertebrates as ants and insect larvae. No significant relationships were found between body size, number of prey eaten or volume consumed. The juvenile, male and female M. t. icae not showed significant differences regarding number of ants or insect larvae consumed, neither on the proportion consumed of plant material. However, total volume of plant material was different between males and females, compared to juveniles. Multivariate analysis showed no evident difference in the diets of juveniles, males and females. Trophic niche amplitude for M. t. icae was Bij = 6.97. The consumption of plant material and invertebrates is important for both juvenile and adult iguanas, therefore; no clear age difference in diet was observed in the individuals studied. This species would present great diet plasticity (omnivory) influenced by the local variation of food resources. Possible consequences of a varied diet may include particular characteristics of its parasites, foraging strategies and efficiency, thermoregulation, morphology, among others.